2014
DOI: 10.1089/adt.2014.606
|View full text |Cite
|
Sign up to set email alerts
|

A ZebrafishIn VivoPhenotypic Assay to Identify 3-Aminothiophene-2-Carboxylic Acid-Based Angiogenesis Inhibitors

Abstract: Small molecules that inhibit angiogenesis are attractive drug candidates for cancer, retinopathies, and age-related macular degeneration. In vivo, phenotypic screening in zebrafish (Danio rerio) emerges as a powerful methodology to identify and optimize novel compounds with pharmacological activity. Zebrafish provides several advantages for in vivo phenotypic screens especially for angiogenesis, since it develops rapidly, externally, and does not rely on a functional cardiovascular system to survive for severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…In vivo phenotypic screens using zebrafish embryos have been particularly valuable in identifying novel bioactive natural compounds or optimizing the activity of lead compounds [ 19 ]. Chemical library screens using zebrafish embryos for the identification of melanogenesis inhibitors [ 20 ] and or transgenic-based screens for angiogenesis [ 21 ] or neoglucogenesis [ 18 ] have been very productive.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo phenotypic screens using zebrafish embryos have been particularly valuable in identifying novel bioactive natural compounds or optimizing the activity of lead compounds [ 19 ]. Chemical library screens using zebrafish embryos for the identification of melanogenesis inhibitors [ 20 ] and or transgenic-based screens for angiogenesis [ 21 ] or neoglucogenesis [ 18 ] have been very productive.…”
Section: Introductionmentioning
confidence: 99%
“…This core is, indeed, a well-known bioisostere of anilines used in drug design and can be found in agrochemicals such as in dimethenamid [2] and penthiopyrad, [3] showing herbicidal and fungicidal activity respectively, and also in pharmaceuticals like the local anesthetic articaine [4] or telenzepine [5,6] which is used for the treatment of peptic ulcer (Figure 1). Moreover, according to recent studies, this scaffold is present in potent inhibitors of hepatitis C virus [7,8] and tumor growth, [9,10] as well as in anti-inflammatory [11] and anti-microbial [12] compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish is a popular vertebrate model that has been extensively used on phenotypic screens for bioactive compounds ( Papakyriakou et al, 2014 ; MacRae and Peterson, 2015 ). By employing a fast and robust zebrafish screen, we identified that the dibenzofuran compounds isolated from C. pycnoloba exhibit strong inhibition of melanogenesis.…”
Section: Discussionmentioning
confidence: 99%